P262 Tiotropium Safety And Performance In Respimat® (tiospir™): Safety And Efficacy In Patients With Tiotropium Handihaler® Use At Baseline. (10th November 2014) - Calverley, P; Anzueto, A; Dahl, R; Mueller, A; Fowler, A; Metzdorf, N; Wise, R; Dusser, D
Abstract : Introduction: The TIOSPIR™ trial showed that tiotropium Respimat ® and HandiHaler ® have similar safety and exacerbation efficacy profiles in patients with chronic obstructive pulmonary disease (COPD). We present here results for patients from the United States (US) using tiotropium HandiHaler ® at baseline. Methods: TIOSPIR™ (n = 17, 135), a 2–3 year, randomised, double-blind, parallel-group, event-driven trial, compared safety and efficacy of once-daily tiotropium Respimat ® 5 and 2.5 µg with once-daily HandiHaler ® 18 µg in patients with COPD. Primary endpoints were time to death and time to first COPD exacerbation. Safety, including cardiovascular safety, was assessed. Tiotropium Respimat ® was unavailable in the US (baseline tiotropium HandiHaler ® use only), therefore this subgroup was analysed. Results: Overall, 1779 patients from TIOSPIR™ treated with tiotropium HandiHaler ® 18 µg at baseline in the US were randomised and treated (n = 572, n = 602 and n = 605 for tiotropium Respimat ® 2.5 and 5 µg and HandiHaler ® 18 µg). A numerically lower time to death was observed for patients within the Respimat ® groups versus HandiHaler ® (vital status follow up: Respimat ® 5 µg: hazard ratio [HR], 0.77; 95% confidence interval [CI], 0.53–1.12; Respimat ® 2.5 µg: HR, 0.76; 95% CI, 0.52–1.12). Risk of major adverse cardiovascular event (MACE) and fatal MACE was numerically lower for the Respimat ® groups versus HandiHaler ® (MACE: Respimat ® 5 µg: HR, 0.69; 95% CI, 0.41–1.18; Respimat ® 2.5 µg: HR, 0.83; 95% CI, 0.50–1.39; fatal MACE: HR, 0.60; 95% CI, 0.26–1.37; Respimat ® 2.5 µg: HR, 0.42; 95% CI, 0.16–1.09). Overall incidence of a fatal event (on-treatment) was lower in the Respimat ® groups versus HandiHaler ® (Respimat ® 5 µg: HR, 0.60; 95% CI, 0.39–0.92; Respimat ® 2.5 µg: HR, 0.67; 95% CI, 0.44–1.02). Time to first exacerbation was similar across groups (Respimat ® 5 µg versus HandiHaler ® : HR, 0.94; 95% CI, 0.82–1.08). Conclusions: Patients treated with tiotropium HandiHaler ® 18 µg at baseline, and who were randomised and subsequently received tiotropium Respimat ® 2.5 or 5 µg, had a similar risk of exacerbation as patients who continued to be treated with tiotropium HandiHaler ® 18 µg. In this subgroup of patients, all-cause mortality was similar between tiotropium Respimat ® and HandiHaler ® 18 µg. Abstracts M263 to M272 are found on page A218–A223: